1991
DOI: 10.1088/0953-4075/24/3/021
|View full text |Cite
|
Sign up to set email alerts
|

Triply differential cross sections for ionization of hydrogen atoms by electrons: the intermediate and threshold energy regions

Abstract: Triply ditkrential cross sections in coplanar geometry for the ionization of alomic hydrogen by electron impact have been measured and calculated at incident electron energies of 54.4, 27.2, 17.6 and 15.6 eV. The theory is the same as that used successfirlly at higher energies arid is shown to repioduce nearly all features of the CTOS sections in this low-energy regime as well. Moreovcr, the physical origin of peaks and dips in the triply differential cross sections has been explained. We conclude that kinemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
76
5

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 23 publications
8
76
5
Order By: Relevance
“…In these studies, several models were tested for improving the description of the final state: (i) the Coulomb Born approximation (CBA) model (in which the ejected electron is described by a Coulomb wave, whereas the incident and the scattered electrons are described by plane waves); (ii) the distorted wave Born approximation (DWBA) model in which the ejected electron was described by means of a distorted wave function calculated by numerical resolution of the Schrödinger equation where distortion effects between the ejected species and the ionized target were introduced; (iii) the two-Coulomb-wave (2CW) model where the scattered and the ejected electrons were both described by target Coulomb waves; and finally (iv) the BBK model (see Brauner et al [26]) where the final state is described by the product of three Coulomb waves, which take into account the interaction between the scattered electron and the residual target, that between the ejected electron and the residual target and that between the scattered electron and the ejected one, respectively. However, as explained in Champion et al [24], all these sophisticated descriptions are essentially needed for experimental configurations in which the ejected velocity v e matches the scattered velocity v s and consequently do not concern the case here investigated.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In these studies, several models were tested for improving the description of the final state: (i) the Coulomb Born approximation (CBA) model (in which the ejected electron is described by a Coulomb wave, whereas the incident and the scattered electrons are described by plane waves); (ii) the distorted wave Born approximation (DWBA) model in which the ejected electron was described by means of a distorted wave function calculated by numerical resolution of the Schrödinger equation where distortion effects between the ejected species and the ionized target were introduced; (iii) the two-Coulomb-wave (2CW) model where the scattered and the ejected electrons were both described by target Coulomb waves; and finally (iv) the BBK model (see Brauner et al [26]) where the final state is described by the product of three Coulomb waves, which take into account the interaction between the scattered electron and the residual target, that between the ejected electron and the residual target and that between the scattered electron and the ejected one, respectively. However, as explained in Champion et al [24], all these sophisticated descriptions are essentially needed for experimental configurations in which the ejected velocity v e matches the scattered velocity v s and consequently do not concern the case here investigated.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These showed that the shapes of the angular distributions depend on the target even though the asymptotic Coulomb fields experienced by the three final state particles are target independent. While theoretical calculations [3][4][5][6] were able to replicate reasonably well the experimentally observed (e, 2e) angular distributions, the first absolute measurements, for He [7,8], agreed with only two of these [4,6]. The implicit implication was that accurate accounting of target effects on the various electronic partial waves as well as treatment of electronelectron interactions are necessary to obtain agreement with absolute data and that omission of these effects can lead to disagreement with experiment by factors of 2-200 [9].…”
mentioning
confidence: 99%
“…At the 54.4-eV projectile energy there are unnormalized relative measurements of the TDCS for four angles of the fast electron and one energy of the slow electron [17].Here Jones et al [15],following the work of Brauner, Briggs, and Klar [14] and Brauner et al [17] that it is not necessary to satisfy the final-state boundary condition if the initial-state boundary condition is satis e .…”
mentioning
confidence: 99%